Non-toxic layered double hydroxide nanoplatelet dispersions for gas barrier coatings on flexible packaging. Issue 8 (17th March 2021) - Ruengkajorn, Kanittika; Chen, Chunping; Yu, Jingfang; Buffet, Jean-Charles; O'Hare, Dermot
Abstract : A green synthesis of well dispersed LDH nanosheets via a reconstruction process in concentrated amino acid solution was reported. The LDH nanosheet/PVA coated PET films exhibited excellent optical response and high oxygen barrier (0.35 cc m −2 day −1 ). Abstract : High gas barrier, transparent and non-toxic coatings are in increasing demand due to the need to develop easier recyclable food packaging technologies. Herein, we report a green synthesis of layered double hydroxide (LDH) nanoplatelets via a reconstruction process in concentrated amino acid solution. The effect of both the amino acid (nonpolar and polar) and the original LDH morphology (rosette and large platelet) on the formation of uniform dispersed LDH nanoplatelets was systematically studied. LDH nanosheet dispersions in polyvinyl alcohol (PVA) were coated on polyethylene terephthalate (PET) substrates. The oxygen barrier performance and optical properties of the LDH nanosheet coated PET films were evaluated. We found that the PET coated films retained excellent optical responses and exhibited a high oxygen barrier, with an oxygen transmission rate down to 0.35 cc m −2 day −1 . This represents an oxygen barrier improvement factor (BIF) between the coated and uncoated PET films of 175.